Epidemiology of myelofibrosis, essential thrombocythemia, and polycythemia vera in the European Union. (3rd February 2014) - Moulard, Odile; Mehta, Jyotsna; Fryzek, Jon; Olivares, Robert; Iqbal, Usman; Mesa, Ruben A.
Abstract Background Primary myelofibrosis (PMF), essential thrombocythemia (ET), and polycythemia vera (PV) are BCR ABL‐negative myeloproliferative neoplasms (MPN). Published epidemiology data are scarce, and multiple sources are needed to assess the disease burden. Methods We assembled the most recent information available on the incidence and prevalence of myelofibrosis (MF), ET, and PV by conducting a structured and exhaustive literature review of the published peer‐reviewed literature in EMBASE and by reviewing online documentation from disease registries and relevant health registries in European countries. The search was restricted to human studies written in English or French and published between January 1, 2000, and December 6, 2012. Results Eleven articles identified from EMBASE, three online hematology or oncology registries, and two Web‐based databases or reports were used to summarize epidemiological estimates for MF, PV, and ET. The incidence rate of MF ranged from 0.1 per 100 000 per year to 1 per 100 000 per year. Among the various registries, the incidence of PV ranged from 0.4 per 100 000 per year to 2.8 per 100 000 per year, while the literature estimated the range of PV incidence to be 0.68 per 100 000 to 2.6 per 100 000 per year. The estimated incidence of ET was between 0.38 per 100 000 per year and 1.7 per 100 000 per year. While a few studies reported on the MPNs' prevalences, it is difficult to compare them as various types of prevalence were calculated (point prevalence vs. period prevalence) and standardization was made according to different populations (e.g., the world population and the European population). Conclusion There is a wide variation in both prevalence and incidence estimates observed across European data sources. Carefully designed studies, with standardized definitions of MPNs and complete ascertainment of patients including both primary and secondary MFs, should be conducted so that estimates of the population aimed to receive novel treatments for these neoplasms are better understood assist public health planning and provide valuable information about the burden of illness to policy makers, funding agencies, resource planners, healthcare insurers, and pharmaceutical manufacturers.